Confidentiality, disclosure and doping in sports medicine - McNamee, M.; Phillips, N. (British Journal of Sports Medicine, 2011)
The manner in which healthcare and medical professionals serve their athlete patients is governed by a variety of relevant codes of conduct. A range of codified rules is presented that refer both the welfare of the patient and the maintaining of confidentiality, which is at the heart of trustworthy relations. The 2009 version of the World Anti-Doping Code (WADC), however, appears to oblige all healthcare professionals not to assist athletes if they are known to be engaged in doping behaviours under fear of removal from working with athletes from the respective sports. In contrast, serving the best interests of their athlete patients may oblige healthcare professionals to give advice and guidance, not least in terms of harm minimisation. In so far as the professional conduct of a healthcare professional is guided both by professional code and World Anti-Doping Code, they are obliged to fall foul of one or the other. We call for urgent and pressing inter-professional dialogue with the World Anti-Doping Agency to clarify this situation.